TopTV : changing the face of the South African pay-tv landscape - Townsend, Stephanie (SAGE knowledge. Cases., 2016)
When TopTV commenced services on 1 May 2010, MultiChoice's DStv had been the dominant player for 15 years. TopTV made a calculated decision to target clients who had not been able to afford pay-TV. This included 60% of South Africans who wanted wholesome, family entertainment but were not particularly interested in sport, which was a major part of DStv's offering. TopTV had since extended its target market to include the LSM 6-9 income bracket. Nonetheless, Vino Govender, CEO of TopTV, wondered whether this repositioning was sustainable enough to compete successfully in the marketplace.